Creating Positive Futures 2024 - Menon, Jaime; Steen, Jan (My University, 2025)
Summary of the 2024 activities of the Kansas PRIDE program now known as Kansas Community Empowerment and affiliated communities.
Keywords: Administrative and Research Reports; Community Development; Creating Positive Futures